Implementasi Pendidikan Karakter Pada Mata Pelajaran Aqidah Akhlak di SMP IT Swasta Ashabul Yamin Aceh Tenggara - Maulidah, Laili; Nasution, Mawaddah (Universitas Labuhanbatu, 2024)
The aim of this research is to find out how the process of implementing moral aqidah learning is carried out and how the methods of habituation, advice and example are in character formation, supporting factors and inhibiting factors in learning moral aqidah. This research uses a qualitative approach method. Data collection techniques using interview, observation and documentation methods. Data analysis techniques using methods data collection, Data reduction, data presentation and data conclusion. The results of this research include: The implementation of aqidah akhlak learning at the private Asbabul Yamin IT Middle School in Southeast Aceh is running well in accordance with the existing curriculum, The method of habituation, advice and example is running well Supporting factors from This implementation is parents and the inhibiting factor for this implementation is the inadequate facilities and infrastructure of the school which causes students to lack understanding of the learning provided, Effect of Implementation Methods of habituation, advice and example in learning moral beliefs have a good influence, namely students are more disciplined and active in studying, respectful and polite to teachers and parents, get used to obeying the rules in the madrasa and there are no more students fighting.